2017
DOI: 10.1371/journal.pone.0183860
|View full text |Cite
|
Sign up to set email alerts
|

Mother-to-child transmission of HIV in Kenya: A cross-sectional analysis of the national database over nine years

Abstract: ObjectiveTo describe factors associated with mother-to-child HIV transmission (MTCT) in Kenya and identify opportunities to increase testing/care coverage.DesignCross-sectional analysis of national early infant diagnosis (EID) database.Methods365,841 Kenyan infants were tested for HIV from January 2007-July 2015 and results, demographics, and treatment information were entered into a national database. HIV risk factors were assessed using multivariable logistic regression.Results11.1% of infants tested HIV pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…A total of nine countries and 33 studies were included in this systematic review and meta-analysis. Of this, sixteen studies were from Ethiopia (5-11, 21-24, 26-28, 37, 38 ), five studies were from Kenya [ 12 , 15 , 20 ], three studies were from Tanzania [ 13 , 16 ], three studies were from Uganda [ 14 , 18 , 19 , 31 ], two studies were from Zimbabwe [ 33 , 34 ], and the remaining one study was from Eritrea [ 19 ], South Sudan [ 32 ], Malawi [ 35 ], and Rewanda [ 36 ]. In this review, eighteen studies were cross-sectional study designs while fifteen studies were cohorts (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of nine countries and 33 studies were included in this systematic review and meta-analysis. Of this, sixteen studies were from Ethiopia (5-11, 21-24, 26-28, 37, 38 ), five studies were from Kenya [ 12 , 15 , 20 ], three studies were from Tanzania [ 13 , 16 ], three studies were from Uganda [ 14 , 18 , 19 , 31 ], two studies were from Zimbabwe [ 33 , 34 ], and the remaining one study was from Eritrea [ 19 ], South Sudan [ 32 ], Malawi [ 35 ], and Rewanda [ 36 ]. In this review, eighteen studies were cross-sectional study designs while fifteen studies were cohorts (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of ten studies [ 6 , 7 , 9 , 10 , 15 , 21 , 25 , 27 , 38 ] were included in this meta-analysis to show the significance between mixed feeding and MTCT of HIV. The pooled odds ratio showed that mothers practiced mixed feeding for their exposed infants were 6.22 times more likely to acquire HIV infection than exclusively breastfeeding exposed infants (AOR = 6.22 (1.02, 11.41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kenya, a country with one of the largest HIV epidemics in the world in terms of the number of people living with HIV [13], data from 2018 shows that the overall adult HIV prevalence (~5%) and incidence (36,000 new infections annually) continues to decline, but HIV related deaths continue to plateau [14,15]. Additionally, without treatment and adherence, the risk of mother to child transmission (MTCT) of HIV among HIV positive pregnant women increases [16][17][18][19], with coverage at 74%, down from 86% [20]. While virtual elimination of MTCT is possible [21], this scenario presents the need to not only focus on access to ART and outcomes along the HIV cascade, but also to begin to institute a health systems approach focusing on financing, human resources, service delivery, and information and appropriate technology for comprehensive HIV treatment and prevention [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Mother-to-child transmission accounts for almost all new infections in children [5]. Without uptake of effective interventions, HIV-infected mothers will continue to infect their children [6,7,8].…”
Section: Introductionmentioning
confidence: 99%